2019
DOI: 10.1042/bsr20190787
|View full text |Cite|
|
Sign up to set email alerts
|

Functional analyses of microRNA-326 in breast cancer development

Abstract: MicroRNA-326 (miR-326) was reported to be dysregulated and involved in the progression of multiple cancers. However, the clinical significance, biological role and underlying mechanism of miR-326 in the carcinogenesis of breast cancer are still unclear. In the present study, we showed that miR-326 was down-regulated in human breast cancer tissues and cell lines. Our results also revealed that miR-326 overexpression significantly suppressed breast cancer cell proliferation, migration and invasion, and induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Likewise, previous evidence has shown that miR-326 may act as an anti-tumor miR in the occurrence and development of human prostatic carcinoma (10). Consistent with our findings, miR-326 was down-regulated in the tissues and cell lines of human BC, and the overexpressed miR-326 has been showed to inhibit the cell proliferation, migration, and invasion of BC (11). Besides, miR-326 has been reported to be poorly expressed in gastric cancer cells and overexpression of miR-326 inhibits the proliferation of gastric cancer cells (29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, previous evidence has shown that miR-326 may act as an anti-tumor miR in the occurrence and development of human prostatic carcinoma (10). Consistent with our findings, miR-326 was down-regulated in the tissues and cell lines of human BC, and the overexpressed miR-326 has been showed to inhibit the cell proliferation, migration, and invasion of BC (11). Besides, miR-326 has been reported to be poorly expressed in gastric cancer cells and overexpression of miR-326 inhibits the proliferation of gastric cancer cells (29).…”
Section: Discussionsupporting
confidence: 92%
“…miR-326 highlights itself as an antioncomiR in pro-static carcinoma by negatively regulates Mucin1 (10). Additionally, miR-326 has been noted to harbor tumor-suppressive property in BC (11). Furthermore, the TargetScan database revealed that there were binding sites between miR-326 and ETS-domain containing protein (ELK1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the levels of miR-326 are lower in breast cancer tissues (32,33). In particular, a recent study by our team found that miR-326 functions as a tumor suppressor in breast cancer by targeting SOX12 (34). The RT-qPCR results showed that overexpression of miR-326 significantly decreased SNHG3 expression whereas depletion of SNHG3 obviously increased miR-326 levels in the assayed cells.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, miR-326 targets ErbB/PI3K and SOX12 to repress BC cell proliferation, migration and invasion. 14,15 It should be noted that circRNAs participate in affecting tumor progression by interacting with miRNAs. 35 There are also accumulating studies demonstrating that circRNA adsorbs miRNAs, thus taking part in the development in BC.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, some studies indicate that miR-326 is downregulated in BC. 14,15 This implies that miR-326 functions as the tumor suppressor in BC. It is worth noting that bioinformatics predicts the potential binding site between circ_0000291 and miR-326, suggesting that circ_0000291 may regulate the expression of miR-326, but this mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%